PERANCANGAN VIDEO PROMOSI PORTBLUE SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Karim, Malik Abdul; Martono, Siswo; Riqqoh, Abdullah Khoir (Jurnal Art Nouveau, 2018)
Along with the development of creative industry in Indonesia especially Leather Shoes, competition between brands can not be inevitable anymore. The emergence of other brands such as Brodo with the advantages and uniqueness of the past made it tighter. Portblue shoes as one of the leather shoes brands that stood at the end of 2015, will be competing from the tight competitors in the leather shoe industry. portblue issued some new shoe models, the shoes with the type of shoes that just released. Boots shoes are not only for lower work but have grown to be a support for making Shoes can be used in many other places.